2000
DOI: 10.1046/j.1365-2648.2000.01628.x
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experience of suffering repeated severe attacks of acute intermittent porphyria

Abstract: The aim of this study was to elucidate the experiences of the women with severe, recurrent attacks of porphyria and how they coped with them successfully. A total of five women were interviewed and were encouraged to describe their experiences. Thematic content analysis was used to interpret the significance of their narratives. The result demonstrated that the women's experience was of living in deepest darkness with inexpressible pain, both physical and mental. Coming into contact with health care had its go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Having to adjust to the “new normal” proved to be an issue for all patients; however, when referred to psychiatrists/psychologists to help cope, some expressed resentment. This has been reported previously as patients with recurrent attacks did not want to be viewed as having a mental illness 18 . Other patients stated this helped them manage their disease, specifically by providing new coping methods.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Having to adjust to the “new normal” proved to be an issue for all patients; however, when referred to psychiatrists/psychologists to help cope, some expressed resentment. This has been reported previously as patients with recurrent attacks did not want to be viewed as having a mental illness 18 . Other patients stated this helped them manage their disease, specifically by providing new coping methods.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, physicians should focus on identifying patient-specific barriers to seeking early treatment to prevent progression to a severe attack requiring hospitalization. As noted previously 18 , these patients cited previous poor or difficult clinical experiences when discussing the causes of their treatment avoidance. Although documentation confirming the diagnosis can be useful when presenting to new physicians, these patients struggled with the severity of their symptoms not being recognized.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…A qualitative study from Sweden, in which five women were interviewed on their experiences with serious AIP attacks, concluded that when these women had their attacks they lived in the ''deepest darkness'', with indescribable pain, both physically and mentally (Wikberg et al 2000). A British questionnaire study of 116 patients (Millward et al 2001) found lower quality of life in patients with AIP, compared to patients with other types of porphyria.…”
Section: Previous Researchmentioning
confidence: 99%